Поширення Реформації на теренах східної Словаччини у XVI столітті та її вплив на суспільно-політичне життя Закарпаття - Борис, І. (Міжнародні зв’язки України: наукові пошуки і знахідки, 2019)
У статті висвітлюється проблема поширення на східнословацьких
землях великого релігійного та суспільно-політичного руху, відомого як
європейська Реформація. Простежується процес прийняття правових релігійних засад та розглядаються спроби упорядкувати духовне життя населення регіону. На терени Словаччини Реформація проникла на початку 20-х рр.
XVI ст. Разом зі змінами, що спостерігаються при реформуванні суспільно-політичного життя на словацьких землях, відбуваються і зміни в
культурному та релігійному житті країни. Протягом XVI ст. на словацьких землях відбувається поширення нових релігійних течій, що мали
пряме відношення до європейської Реформації. Як відомо, реформаційні
процеси призвели до розколу римо-католицької церкви та утворення
нових віровчень. Вони проявлялися різною мірою практично в усіх країнах
католицького світу. Нові віросповідні положення позначилися на становищі церкви як великого землевласника та складової феодальної системи, зачепивши католицьку церкву як велику ідеологічну силу. Реформація протягом XVI ст. набувала характеру широких релігійних та
соціально-політичних рухів, що висували вимоги реформувати католицьку церкву й докорінно змінити її усталені роками догми та звичаї.
Цей процес не оминув і землі, що нині входять до Закарпатської
області України. Оскільки край перебуває в безпосередній близькості до
Словаччини, доцільним буде розглянути досвід і вплив процесу словацької
Реформації на суспільно-духовне життя тогочасного Закарпаття. The article highlights the issue of dissemination of the religious, social and
political movement widely known as the process of European Reformation on
the territory of Eastern Slovakia. In particular, the author traces back the
process of adopting legal religious principles and the attempts to achieve toplevel
systematization of spiritual life management.
Actually, Reformation penetrated into the territory of Slovakia in the early
1520s. Along with the changes in social and political life occurring in
Slovakian lands, there were changes in cultural and religious life of the
country as well. Throughout the 16th century new religious movements
referring directly to the European Reformation spread all over the territory of
Slovakia. It is common knowledge that the Reformation processes led to
division of the Roman Catholic Church and formation of new religious
doctrines. They were manifested to different extents of efficiency practically in
all the countries of the Catholic world. Establishment of new religious
principles had a significant impact on the position of the church as a big
landowner as well as a component of the feudal system, affecting the role of the
Catholicism as a major ideological power. Throughout the 16th century
Reformation appeared in the form of widespread religious, social and political
movements demanding to reform the Catholic Church and radically change its
conventional dogmata and practices, which had been ingrained for years.
At the end of the century practically all over the territory of the Eastern
Slovakia there were organized Seniorates and appeared the first attempts to
systematize spiritual life management at top level. The first attempts to spread
new religious movements were supported by the population of most eastern
Slovakian cities, which was to a certain extent, an impetus to further
development of the Reformation movement. While Slovaks and Germans longed
for the Lutheran form of the Reformation, Hungarian residents were inclined to
adopt Calvinism and Anabaptism. Thus, crystallization of Reformation was
gradually building up and strengthening its position.
The process mentioned above influenced the lands which are nowadays a
part of Transcarpathian region of Ukraine. As Transcarpathia is located in the
immediate vicinity of Slovakia, it is reasonable to examine the experience and
impact of the process of Slovakian Reformation on the Transcarpathian realia
of those days.